Chemical Control Guide For Diseases of Vegetables Revision No. 15 - Tom Kucharek (EDIS, 2003)
Extension plant pathology report No. 6 Gainesville, Florida, November, 2002. The purpose of this listing is to guide you with legal use of sprayable plant disease control chemicals.